A data envelopment analysis of Sharia stock listed companies on the Jakarta Islamic Index - Suryomurti, Wiku; Surur, Miftakhus; Akbar, Nashr; Maulida, Syahdatul (Jurnal Ekonomi & Keuangan Islam, 2026)
Purpose – This study analyzes the efficiency of companies listed on the Jakarta Islamic Index (JII) during the 2020–2023 period. Method – This study applies data envelopment analysis (DEA) using total assets, equity, and operational expenses as input variables, with market capitalization and earnings per share (EPS) as output variables. Market capitalization is employed to capture a firm’s ability to convert internal resources into market-recognized value as shaped by investor perception.Findings – The results indicate that most JII companies operate inefficiently, with efficiency scores below 0.2. Several benchmark firms form the efficiency frontier: Adaro Energy Indonesia (2022), Indo Tambangraya Megah (2022), Bumi Resources Minerals (2021), Unilever Indonesia (2021), and Aspirasi Hidup Indonesia (2021). The sector-wise analysis indicates that the financial sector exhibits the highest and most consistent scale efficiency. In contrast, from an industrial perspective, the transportation and energy sectors demonstrate the most optimal efficiency performance. Regarding ownership structure, state-owned enterprises consistently achieve higher scale efficiency than privately owned companies. Further analysis suggests that efficiency improvements are primarily driven by output performance, particularly market capitalization, highlighting the relevance of an output-oriented approach to long-term efficiency strategies. Implications – This perspective suggests that efficiency in Sharia Stock Listed Companies depends not only on internal management performance, but also on external market perceptions that determine their market value. Originality – This study offers originality by employing DEA approach to assess the efficiency of Sharia stock-listed companies in the JII, integrating sectoral, industrial, and ownership perspectives that have received limited attention in prior research.